2010
DOI: 10.1590/s0101-60832010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Ausência de relação entre hipertensão arterial sistêmica e desempenho cognitivo em idosos de uma comunidade

Abstract: ResumoContexto: Pesquisas documentam que a hipertensão arterial pode estar envolvida no declínio cognitivo em pacientes idosos. Estima-se que até 60% dos idosos apresentem hipertensão arterial, tornando-os mais suscetíveis ao declínio cognitivo. Objetivo: Investigar a relação entre hipertensão arterial e desempenho cognitivo em idosos não portadores de demências ou depressão. Método: A amostra foi constituída por idosos participantes de pesquisa populacional em andamento sobre envelhecimento no município de Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
13
0
3
Order By: Relevance
“…Studies that investigated the impact of antihypertensive treatment on the correlation between hypertension and cognition have produced controversial results. 10,16,17 It is assumed that untreated hypertension is a predictor for cognitive decline and the use of antihypertensive drugs is a protector of cognitive function. Di Nucci et al 10 reported no significant abnormalities in the cognition of hypertensive elderly individuals who used antihypertensive medication on a regular basis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that investigated the impact of antihypertensive treatment on the correlation between hypertension and cognition have produced controversial results. 10,16,17 It is assumed that untreated hypertension is a predictor for cognitive decline and the use of antihypertensive drugs is a protector of cognitive function. Di Nucci et al 10 reported no significant abnormalities in the cognition of hypertensive elderly individuals who used antihypertensive medication on a regular basis.…”
Section: Discussionmentioning
confidence: 99%
“…Education levels have been reported as one of the most significant determinants of cognitive decline in several studies of the factors associated with this phenomenon. [6][7][8]10,11 Other factors have also been highlighted, such as gender, marital status, smoking and alcohol consumption. 12 Therefore, cognitive dysfunction is determined by a complex association of factors, including individual and social conditions, and can directly affect the quality of life of the elderly individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, studies are needed to investigate risk factors associated with this decline. Such aspect is due to knowing that the decline will affect the performance of daily life activities, generating great impact on social and occupational activities of individuals (9) . Thus, early identification of cognitive decline may help to create strategies to promote cognitive activities, in order to slow the impact on the individuals' daily life (10) .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have reached contrasting conclusions regarding the effects of antihypertensive treatment on hypertension and cognitive decline [20][21][22] . The results of Holanda et al 23 found that hypertensive elderly individuals are at greater risk of cognitive function decline than normotensive elderly persons.…”
mentioning
confidence: 99%